Associations of IL6 polymorphisms with lung function decline and COPD. Issue 8 (8th April 2009) - He, J-Q; Foreman, M G; Shumansky, K; Zhang, X; Akhabir, L; Sin, D D; Man, S F P; DeMeo, D L; Litonjua, A A; Silverman, E K; Connett, J E; Anthonisen, N R; et al.
Abstract : Background: Interleukin-6 (IL6) is a pleiotropic pro-inflammatory and immunomodulatory cytokine which probably plays an important role in the pathogenesis of chronic obstructive pulmonary disease (COPD). There is a functional single nucleotide polymorphism (SNP), -174G/C, in the promoter region of IL6 . It was hypothesised that IL6 SNPs influence susceptibility for impaired lung function and COPD in smokers. Methods: Seven and five SNPs in IL6 were genotyped in two nested case-control samples derived from the Lung Health Study (LHS) based on phenotypes of rate of decline of forced expiratory volume in 1 s (FEV1 ) over 5 years and baseline FEV1 at the beginning of the LHS. Serum IL6 concentrations were measured for all subjects. A partially overlapping panel of nine IL6 SNPs was genotyped in 389 cases of COPD from the National Emphysema Treatment Trial (NETT) and 420 controls from the Normative Aging Study (NAS). Results: In the LHS, three IL6 SNPs were associated with decline in FEV1 (0.023⩽p⩽0.041 in additive models). Among them, the IL6 _-174C allele was associated with a rapid decline in lung function. The association was more significant in a genotype-based analysis (p = 0.006). In the NETT-NAS study, IL6 _-174G/C and four other IL6 SNPs, all of which are in linkage disequilibrium with IL6 _-174G/C, were associated with susceptibility to COPD (0.01⩽p⩽0.04 in additive genetic models). Conclusion: The results suggest that the IL6 _-174G/C SNP is associated with a rapid decline in FEV1 and susceptibility to COPD in smokers.